Housing and indoor factor influencing spread of COVID-19 – a review - Hakimah Yusop,; Sharifa Ezat Wan Puteh, (Penerbit Universiti Kebangsaan Malaysia, 2023)
There has been growing recognition linking spread of COVID-19 with environmental factors. One of the environmental factors with robust epidemiological literature supporting its role in diseases is the housing or built environment. COVID-19 spread has been found to occur mostly at homes through secondary household transmission. As most people spend more times inside homes during the pandemic, household remains an important site of COVID-19 spread. The aim of this study is to examine how housing and indoor factors affect the transmission and spread of COVID-19. This review employed a comprehensive search strategy to gather a broad range of scholarly articles and grey literature to provide a comprehensive understanding of the housing-related aspects of COVID-19 transmission. Three electronic databases (Web of Science, Scopus, and PubMed) were searched using specific keywords related to COVID-19, housing, residents, neighborhoods, and indoor environments. Additionally, a supplementary literature survey was conducted to include relevant grey literature sources. This article summarizes the housing indoor factors involved in COVID-19 transmission, including the role of transmission from contaminated household surfaces. Indoor transmission of COVID-19 is found to be more likely due to contact transmission and close-contact aerosol transmission in a crowded, confined, and poorly ventilated indoor environment, related to poor housing condition. Whilst role of spread through contaminated household surfaces is of low probability. Based on this review, it can be suggested that besides the existing measures including avoiding crowding, close contacts and proper ventilation, specific standards for indoor environmental quality control and housing condition might be required. Housing is a public health issue and healthy housing is of universal concern.